STRATEGI KOMUNIKASI PEMASARAN DALAM MEMBANGUN BRAND AWARENESS PANTAI VIO-VIO DI KOTA BATAM - mar-atu, mar-atu sholihah; Cindoswari, Ageng Rara (LPPM Universitas Putera Batam, 2024)
This research aims to analyze the marketing communication strategies employed by Vio-Vio Beach in building brand awareness and identifying supporting and hindering factors. The study utilizes a qualitative method, conducting interviews with respondents and focusing questions on relevant topics. Informants are selected using purposive snowball sampling until data saturation is achieved, and the research also references the Integrated Marketing Communication (IMC) theory developed by Kotler and Armstrong. Findings reveal that social media platforms such as Instagram, Facebook, and TikTok are effective in increasing brand exposure and engaging followers. Additionally, special events and online contests contribute positively to Vio-Vio Beach's image. However, challenges include intense competition, susceptible online reputation, unpredictable environmental conditions, and accessibility limitations. With focused and collaborative strategies, Vio-Vio Beach has successfully built a strong brand awareness and increased tourist visits, though ongoing efforts are required to overcome barriers and sustain competitiveness in the tourism industry. Keywords: Vio-vio Beach, Brand Awareness, Marketing Communication Strategy.